Gênero e educação popular: um estudo do cursinho popular Emancipa Floresta e sua contribuição para uma pedagogia feminista - Maria Inês de Oliveira Sousa (2023)
This study aims to discuss and analyze the presence of gender issues in the context of Emancipa Floresta, a popular course that is part of Rede Emancipa: Social Movement of Popular Education. Emancipa Floresta has been operating in Belo Horizonte since 2015, and its pedagogical approach is guided by the educational principles proposed by Paulo Freire. In addition, we seek to discuss and analyze the assumptions of popular education, especially in light of Paulo Freire's proposal, as well as the intersection of these assumptions with other social movements, especially feminism, considering the social and political commitment shared by both in the fight against oppressions. To carry out this research, several procedures were used, such as a bibliographical review, analysis of the registration forms of students taking the course between 2022 and 2003, analysis of questionnaires and conducting semistructured interviews with five students from the course, in addition to interviews with the founders and coordinators of Emancipa Floresta. The questionnaires had the objective of knowing and tracing some general characteristics of the students, such as their family socioeconomic situation, school trajectory, and the impacts of race and gender in their contexts. All the information collected was analyzed in order to understand how the course contributes to the general education of its students, especially in relation to gender issues, in addition to the content required in the college entrance exams or the Enem. The research allows us to conclude that within the course the debate on gender issues and other social struggles are present on a daily basis. The course provides space for these discussions to take place and also assumes a position of defense of social minorities, promoting dialogue even in situations of divergence, always with the commitment to defend the social rights of those socially excluded.